Policy development, implementation and evaluation by the AIDS control program in Uganda: a review of the processes - Tumwesigye, Benson T (BioMed Central, 2013)
BACKGROUND: The AIDS Control Program (ACP) in Uganda has spearheaded the national health sector HIV response for the last three decades. ACP has developed, revised and implemented various HIV prevention, care and treatment policies in order to keep interventions relevant to the changing dynamics of the HIV epidemic. However, the ACP team and partners remain concerned about the lengthy policy development processes. This study documented the policy development and revision processes to identify strengths and weaknesses in order to inform adjustments as Uganda embraces the move to ‘zero’ HIV infections. METHODS: Data was collected through a review of the relevant policy documents and key informant interviews with the five program officers involved in the recently developed Safe Male Circumcision (SMC) policy and the recently revised HIV Counseling and Testing (HCT) policy. Qualitative data was analyzed manually using pre-determined themes. RESULTS: Development and revision of the SMC and HCT policies followed similar processes that included a series of meetings between senior management and a selected technical working group. However, the gaps included: i) inadequate awareness of the existence of national policy development and management guidelines; ii) limited engagement of the policy analysis unit in the policy development/revision processes; iii) inadequate tracking and evaluation of the policies before revision or development of new related policies; iv) lack of specific protocols/standard operating procedures (SOPs); and, v) limited indigenous funding for the entire policy development processes which contributed to non-adherence to the anticipated timelines. CONCLUSIONS: Policy development and revision of the SMC and HCT policies followed similar processes. Gaps identified included lack of protocols/SOPs for the processes and limited indigenous funding to support adherence to anticipated timelines. We recommend active involvement of the policy analysis unit in all policy processes. Specific protocols/SOPs for development, analysis, revision, implementation, monitoring, evaluation and impact assessment processes should be developed prior to commencement of the activities.